Tingkat Pengetahuan Siswa/I Kelas 8 pada Penyuluhan Miopia dengan Media Poster di SMPN 119 Jakarta Pusat - Mahendra Milby Febrian Putra Khaerun; Diniwati Mukhtar (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The rapid development of digital technolosgy has significantly increased screen time among adolescents, contributing to a rise in the prevalence of myopia (nearsightedness). Lack of knowledge regarding eye health and preventive behaviors is a major risk factor for the development of refractive errors. In Islamic perspective, maintaining eye health is considered a form of gratitude and responsibility for the blessing of sight (amanah) bestowed by Allah SWT. This study aims to determine the comparison of knowledge levels among 8th-grade students at SMPN 119 Central Jakarta regarding myopia prevention before and after health education via poster media, while also reviewing the topic from an Islamic viewpoint.This research employed a quantitative design with a quasi-experimental approach using a pre-test and post-test design. The sample consisted of 74 students selected using the Slovin formula. The instrument used was a multiple-choice questionnaire to measure knowledge levels. Data were analyzed using univariate and bivariate analysis to identify differences in knowledge scores. The characteristics of respondents were dominated by the 13–14 age group (98.6%) and female gender (58.1%). The results showed an increase in the mean knowledge score from 19.27 in the pre-test to 21.41 in the post-test. Categorically, respondents with "Good" knowledge levels significantly increased from 59.5% (44 students) before education to 85.1% (63 students) after education. Health education using poster media is effective in improving students' knowledge regarding myopia prevention. From an Islamic perspective, these preventive efforts align with religious commands to avoid self-harm and preserve the blessings given by Allah SWT.